Neurofibromatosis Type I and Stromal Tumor with a Multiple Digestive Localization - Amina Chaka; Farouk Ennaceur; Mohamed Amine Tormen; Ibtissem Korbi; Faouzi Noomen; Khadija Zouari (Case Reports in Surgery)
Neurofibromatosis type I (NF1) is also known as von Recklinghausen disease. It is a genetic disorder that affects the growth and development of nerve cell tissue, which is characterized by a multisystem disorder and an increased risk for cancer. The incidence of gastroduodenal stromal tumor during Recklinghausen disease can reach 35% in autopsies and 5% in clinical cases. In our case, the diagnosis of neurofibromatosis type I was made in a middle-aged women initially diagnosed with a pancreaticoduodenal tumor.